2001
DOI: 10.1097/00005537-200105000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Is a Safe and Effective Treatment of Turbinate Hypertrophy

Abstract: Radiofrequency is a safe surgical procedure capable of reducing turbinate volume without altering the nasal mucosa, and causing minimal discomfort for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 11 publications
7
117
0
5
Order By: Relevance
“…Therefore, nasal surgical procedures like SP impairs the MCC during immediate postoperative period. Coste et al [14] observed that the radiofrequency thermal ablation surgery have preserved the nasal mucociliary functions after only one application. Ulusoy et al [15] observed that before the septal surgery, the nasal mucociliary clearance velocity (NMCV) of concave (10.24 ± 3.96 mm/ min) and convex sides (10.78 ± 3.53 mm/min) of the patients were significantly lower than the control group (17.94 ± 2.89 mm/min).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nasal surgical procedures like SP impairs the MCC during immediate postoperative period. Coste et al [14] observed that the radiofrequency thermal ablation surgery have preserved the nasal mucociliary functions after only one application. Ulusoy et al [15] observed that before the septal surgery, the nasal mucociliary clearance velocity (NMCV) of concave (10.24 ± 3.96 mm/ min) and convex sides (10.78 ± 3.53 mm/min) of the patients were significantly lower than the control group (17.94 ± 2.89 mm/min).…”
Section: Discussionmentioning
confidence: 99%
“…In electrocautery there is damage to the surface mucosa resulting in loss of mucociliary function and thereby causing crusting. Radiofrequency achieves both goals by inducing a localized submucosal injury, resulting in fibrosis and tissue contraction while preserving the structure and function of overlying mucosa [4].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Max well 16 des cri bes VAS as easy to use, sen si ti ve, and ac cu ra te when tes ting dif fe ren ces wit hin sub ject com pa ri sons. Lund 17 has al so des cribed the use of li ne ar vi su al sca les in the of fi ce eva lu a ti on of na sal obs truc ti on, no ting they are of gre at va lu e for com pa ring se qu en ti al eva lu a ti ons.…”
Section: Vas Scoresmentioning
confidence: 99%